Herd effects of child vaccination with pneumococcal conjugate vaccine against pneumococcal non-invasive community-acquired pneumonia: What is the evidence? - Cornelis H. van Werkhoven (Taylor & Francis Group, 2017)
Quantification of pneumococcal conjugate vaccines (PCVs) herd effects are mainly performed on invasive pneumococcal disease (IPD) but there is conflicting evidence regarding herd effects of PCVs on non-IPD pneumococcal community-acquired pneumonia. This review summarizes the available literature on herd effects of PCVs on non-IPD pneumococcal community-acquired pneumonia.